Diagnosis of rapidly progressed primary cardiac lymphoma in liver transplant recipient: A case report - Li, Jianghua; Liu, Qiyun; Peng, Quanzhou; Dong, Shaohong (Frontiers in Oncology, 2022)
Primary cardiac lymphomas (PCLs) are extremely rare and affect the heart. Patients with PCLs usually have delayed diagnosis and treatment. As a consequence, their prognosis is quite unfavorable, and their median survival is approximately 7 months. Herein, we report a 64-year-old man who underwent liver transplantation, presented with chest pain and exertional dyspnea, developed a huge cardiac mass within 2 months, and passed away on day 3 of hospitalization. Histological examination revealed diffuse large B cell lymphoma (DLBCL), which is a rare cardiac tumor with poor prognosis. In this case, DLBCL was only detected postmortem. The extension of the mass and its relationship with the heart were explored with noninvasive cardiac imaging. Despite the rarity of DLBCL, it should be considered in the differential diagnosis of cardiac tumor.